2021
DOI: 10.1038/s41467-021-24656-x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay and cooperation between SREBF1 and master transcription factors regulate lipid metabolism and tumor-promoting pathways in squamous cancer

Abstract: Squamous cell carcinomas (SCCs) comprise one of the most common histologic types of human cancer. Transcriptional dysregulation of SCC cells is orchestrated by tumor protein p63 (TP63), a master transcription factor (TF) and a well-researched SCC-specific oncogene. In the present study, both Gene Set Enrichment Analysis (GSEA) of SCC patient samples and in vitro loss-of-function assays establish fatty-acid metabolism as a key pathway downstream of TP63. Further studies identify sterol regulatory element bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 84 publications
1
55
0
1
Order By: Relevance
“…A large number of studies have reported that TP63 can be used as a prognostic factor for cancers such as salivary gland adenoid cystic carcinoma, anaplastic large cell lymphoma, and squamous cell carcinoma ( 55 58 ). The following analysis demonstrated that TP63 as an autophagy-related gene is a low-risk factor for the prognosis of breast cancer, that is, the lower the expression of TP63, the worse the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have reported that TP63 can be used as a prognostic factor for cancers such as salivary gland adenoid cystic carcinoma, anaplastic large cell lymphoma, and squamous cell carcinoma ( 55 58 ). The following analysis demonstrated that TP63 as an autophagy-related gene is a low-risk factor for the prognosis of breast cancer, that is, the lower the expression of TP63, the worse the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation analysis of FASN provides us more methods to modify fatty acid metabolism in BC ( Figure 8B ). Importantly, the TF most significantly involved in FASN regulation, SREBF1, also plays an important role in lipid metabolism ( 45 , 46 ). Recent studies also reported that multiple lncRNAs competitively bind miRNAs to regulate FASN expression in nasopharyngeal and endometrial cancer ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent GRN analysis showed that endothelial cells were regulated by SREBF1, ZNF585A, and HOXB5, and the remarkable expression of exosome marker genes was observed in both malignant and endothelial cell subpopulations. Among them, SREBF1 appears to be associated with cancer [45] but is rarely reported in HCC, All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent GRN analysis showed that endothelial cells were regulated by SREBF1, ZNF585A, and HOXB5, and the remarkable expression of exosome marker genes was observed in both malignant and endothelial cell subpopulations. Among them, SREBF1 appears to be associated with cancer [45] but is rarely reported in HCC, whereas HOXB5 promotes HCC metastasis by targeting FGFR4 and CXCL1 [46] . HCC-derived exosomes are the main drivers of pre-metastatic ecotone formation and can mediate the metastasis of tumor cells to specific organs [47, 48] .…”
Section: Discussionmentioning
confidence: 99%